2022
DOI: 10.1007/s12020-022-03077-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of the etiological spectrum of bilateral adrenal lesions: A large retrospective, single-center study

Abstract: Purpose: To investigate the clinical characteristics, endocrinological function, and etiologies of patients with bilateral adrenal lesions.Methods: A retrospective study of 777 patients with bilateral adrenal lesions was conducted at the Chinese General Hospital of the People's Liberation Army between January 2013 and January 2018. Patient demographic features, hormonal pro les, imaging ndings, and histopathological ndings were reviewed from the database records.Results: Of the 777 patients with bilateral adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Bilateral adrenal disease also relates to aldosterone and cortisol excess. One study from 2022 of 777 patients (495/777 were males) with bilateral adrenal tumours showed that PA and PBMAH are the most frequent hormonally active lesions (16.6% with PA, and 8.8% with PBMAH) [ 152 ].…”
Section: Approach Of Connshing Syndromementioning
confidence: 99%
“…Bilateral adrenal disease also relates to aldosterone and cortisol excess. One study from 2022 of 777 patients (495/777 were males) with bilateral adrenal tumours showed that PA and PBMAH are the most frequent hormonally active lesions (16.6% with PA, and 8.8% with PBMAH) [ 152 ].…”
Section: Approach Of Connshing Syndromementioning
confidence: 99%
“…PBMAH considered a rare disease in the past, is actually more and more recognized in clinical practice as a heterogeneous clinical entity characterized by a wide spectrum of severity regarding both functional aspects and morphological features. (Bouys et al, 2022;Chevalier et al, 2021;He et al, 2021;Yan et al, 2022).…”
mentioning
confidence: 99%